# Induction Magic: Your Ticket to Inequality Triumph

Welcome to the world of mathematical induction, where we unravel the secrets of inequalities. Inequalities can be quite intimidating, but fear not! We have a powerful tool in our mathematical arsenal: mathematical induction. In this guide, we will embark on a journey to understand how mathematical induction can be your ticket to conquering inequalities with confidence.

## Understanding Mathematical Induction

Let’s begin with the basics. Mathematical induction is a proof technique that helps us establish the truth of mathematical statements, especially when dealing with integers or sequences. It’s like building a chain of stepping stones, each representing a step towards a mathematical truth.

### The Three Steps of Mathematical Induction

Mathematical induction consists of three fundamental steps:

#### Step 1: Base Case

The base case is where we prove the statement for the smallest possible value, typically the lowest integer in the set. It’s like laying the first stone in our path.

#### Step 2: Induction Hypothesis

This step assumes that the statement holds true for some arbitrary integer \(k\). This assumption is crucial for bridging our stepping stones.

#### Step 3: Induction Step

Here, we prove that if the statement holds for \(k\), it must also hold for \(k + 1\). This step is akin to adding more stepping stones to our path, one at a time.

## Mathematical Induction and Inequalities

Now, let’s dive into the fascinating world of using mathematical induction to conquer inequalities. Inequalities are mathematical expressions that show the relationship between two values, often indicating that one is greater than or less than the other. Using induction, we can prove these relationships with ease.

### The Power of Inductive Inequality Proofs

Mathematical induction provides a structured approach to tackling inequalities. Here’s why it’s so powerful:

- It’s systematic: Induction breaks down the proof process into manageable steps, ensuring you don’t miss anything.
- It builds confidence: Following the induction process, you’ll see how each step logically leads to the next, bolstering your confidence in the solution.
- It’s versatile: Induction can be applied to various inequalities, from simple ones to complex mathematical expressions.

## Step-by-Step Guide to Inductive Inequality Proofs

Now, let’s get practical. How do you use mathematical induction to solve inequalities? We’ll walk you through it step by step.

### Step 1: Base Case

In this phase, we’ll establish the inequality for the smallest value in the set. Think of it as laying the foundation for your proof.

### Step 2: Induction Hypothesis

Assume that the inequality holds true for some integer \(k\). This is the equivalent of stepping onto the first stone in your path.

### Step 3: Induction Step

Now comes the exciting part. We’ll prove that if the inequality holds for \(k\), it must also hold for \(k + 1\). This is like adding another stepping stone to your path, inching closer to the finish line.

Let’s illustrate this with an example.

## Example: Triumphing Over Inequalities

**Problem:** Prove that for all positive integers \(n\), the following inequality holds: \( 2^n \gt n \) for \( n \ge 1 \).

**Solution:**

### Step 1: Base Case

For \(n = 1\), the left side of the inequality is \( 2^1 = 2 \), and the right side is \( 1 \). So, the base case holds.

### Step 2: Induction Hypothesis

Assume that the inequality holds for some positive integer \(k\). That is, \( 2^k \gt k \) for \( k \ge 1 \).

### Step 3: Induction Step

We need to prove that if the inequality holds for \(k\), it also holds for \(k + 1\). That is, \( 2^{k+1} \gt k+1 \).

\( \begin{align} 2^{k+1} &=2 \times 2^k \\ &\gt 2 \times k &\color{green}{\text{by the assumption of Step 2}} \\ &= k+k \\ &\gt k+1 \end{align} \)

We have successfully shown that if the inequality holds for \( k \), it also holds for \(k + 1\). This completes the induction step.

## Advanced Techniques and Strategies

While our example was simple, mathematical induction can be applied to more complex inequalities. Here are some advanced techniques and strategies to keep in mind:

**Working with recurrence relations:**Some inequalities involve sequences or recurrence relations. Induction can help you handle these scenarios effectively.**Inequalities with absolute values:**When dealing with absolute value inequalities, consider breaking them down into multiple cases and applying induction to each case.**Polynomial inequalities:**For polynomial disparities, you may need to apply induction to prove specific properties or bounds of the polynomial function.

## Common Pitfalls and How to Avoid Them

As with any mathematical technique, common pitfalls are associated with using induction for inequalities. Here are some to watch out for:

**Incorrect base case:**Ensure that you’ve correctly established the base case. Mistakes here can lead to invalid proof.**Overcomplicating the induction step:**Sometimes, simpler approaches work better. Don’t overcomplicate your induction step if a straightforward one suffices.**Assuming what you need to prove:**Be careful not to assume the very thing you’re trying to prove in the induction step. This is a classic error to avoid.

## Practical Applications

You might wonder, where can I apply this knowledge? Mathematical induction and inequality proofs have practical applications in various fields, including:

**Computer science:**Induction is used to analyze algorithms and prove their correctness.**Physics:**Inequality proofs are essential in physics to establish relationships between variables.**Economics:**Mathematical induction helps economists model complex economic systems.

## Practical Examples

### Example 1

Prove \( 4^{n-1} \gt n^2 \) for \( n \ge 3 \) by mathematical induction.

Step 1: Show it is true for \( n=3 \).

LHS \(=4^{3-1} = 16 \)

RHS \(=3^2=9 \)

LHS > RHS

Therefore it is true for \( n=3 \).

Step 2: Assume that it is true for \( n=k \).

That is, \( 4^{k-1} > k^2 \).

Step 3: Show it is true for \( n=k+1 \).

That is, \( 4^{k} > (k+1)^2 \).

\( \begin{aligned} \displaystyle \require{ASMSymbols} \require{color}

\text{LHS } &= 4^k \\

&= 4^{k-1+1} \\

&= 4^{k-1} \times 4 \\

&\gt k^2 \times 4 &\color{red}{ \text{by the assumption } 4^{k-1} > k^2} \\

&= k^2 + 2k^2 + k^2 &\color{red}{2k^2 > 2k \text{ and } k^2 > 1 \text{ for } k \ge 3} \\

&\gt k^2 + 2k + 1 \\

&= (k+1)^2 \\

&=\text{RHS} \\

\text{LHS } &\gt \text{ RHS}

\end{aligned} \)

Therefore it is true for \( n=k+1 \), assuming that it is true for \( n=k \).

Therefore \( 4^{n-1} \gt n^2 \) is true for \( n \ge 3 \).

### Example 2

Prove \( n^2 \lt 2^n \) for \( n \ge 5 \) by mathematical induction.

*It is quite often used to prove \( A > B \) by \( A-B >0 \). *

Step 1: Show it is true for \( n=5 \).

LHS \( = 5^2 = 25 \)

RHS \( = 2^5 = 32 \)

LHS \( \lt \) RHS

It is true for \( n=5 \).

Step 2: Assume that it is true for \( n=k \).

That is, \( k^2 \lt 2^k \).

Step 3: Show it is true for \( n=k+1 \).

That is, \( (k+1)^2 \lt 2^{k+1}. \)

\( \begin{aligned} \displaystyle \require{ASMSymbols} \require{color}

\text{RHS } – \text{ LHS } &= 2^{k+1}-(k+1)^2 \\

&= 2 \times 2^k-(k^2+2k+1) \\

&\gt 2 \times k^2-(k^2+2k+1) &\color{red}{\text{ by the assumption from Step 2}} \\

&= k^2-2k-1 \\

&= (k-1)^2-2 \\

&\gt 0 &\color{red}{\text{since } k \ge 5 \text{ and so } (k-1)^2 \ge 16} \\

2^{k+1}-(k+1)^2 &\gt 0 \\

(k+1)^2 &\lt 2^{k+1} \\

\end{aligned} \)

Therefore it is true for \( n=k+1 \), assuming it is true for \( n=k \).

Therefore it is true for \( n=k+1 \) is true for \( n \ge 5

### Example 3

A sequence \(S_n\) is defined by \(S_1 = 1, S_2 = 2\) and for \(n \gt 2, S_n = S_{n-1} + (n-1) S_{n-2} \).

(a) Prove \( \sqrt{x} + x \ge \sqrt{x(1 + x)} \) for all real numbers \(x \ge 0 \).

\( \begin{aligned} \require{AMSsymbols} \require{color}

(\sqrt{x} + x)^2 &= x + 2x\sqrt{x} + x^2 \\

(\sqrt{x} + x)^2 &\ge x + x^2 &\color{green} {2x\sqrt{x} \ge 0} \\

\sqrt{x} + x &\ge \sqrt{x+x^2} \\

\therefore \sqrt{x} + x &\ge \sqrt{x(1+x)}

\end{aligned} \)

(b) Hence, prove \( S_n \ge \sqrt{n!} \) for all integers \(n \ge 1 \) using the result of (a).

Step 1: Show it is true for \(S_1\) and \(S_2\).

For \(n = 1, S_1 = 1\) and \(\sqrt{1!} = 1 \).

For \(n = 2, S_2 = 2\) and \(\sqrt{2!} = 1.4142 \ldots \).

Therefore \(S_n \ge \sqrt{n!} \) is true for \(n = 1\) and \(n = 2\).

Step 2: Assume it is true for \(n = k\) and \(n = k-1 \).*Note that two assumptions are required if there are two initial values.*

They are, \(S_{k} \ge \sqrt{k!}\) and \(S_{k-1} \ge \sqrt{(k – 1)!}\).

Step 3: Show it is true for \(n = k + 1\).

That is, \(S_{k+1} \ge \sqrt{(k + 1)!}\).

\( \begin{aligned} \require{AMSsymbols} \require{color}

S_{k+1} &= S_{k} + k S_{k-1} &\color{green} {\text{given}} \\

&\ge \sqrt{k!} + k \sqrt{(k-1)!} &\color{green} {\text{Assumed at Step 2}} \\

&= \sqrt{k(k-1)!} + k \sqrt{(k-1)!} &\color{green} {k! = k(k-1)!} \\

&= \sqrt{(k-1)!}(\sqrt{k} + k) &\color{green} {\text{factorise by } \sqrt{(k-1)!}} \\

&\ge \sqrt{(k-1)!} \sqrt{k(k + 1)} &\color{green} {\text{proved by part (a)}} \\

&= \sqrt{(k + 1)!} \\

\therefore S_{k+1} &\ge \sqrt{(k + 1)!}

\end{aligned} \)

Therefore \(S_n \ge \sqrt{n!} \) is true for all integers \(n \ge 1\).

### Example 4

Prove that \( n! \ge 2^n \) for \( n \ge 4 \).

Step 1: Show it is true for \( n=4 \).

LHS \( = 4! = 24 \)

RHS \( = 2^4 = 16 \)

LHS \( \gt \) RHS

It is true for \( n=4 \).

Step 2: Assume it is true for \( n=k \).

That is, \( k! \ge 2^k \).

Step 3: Show it is true for \( n=k+1 \).

That is, \( (k+1)! \ge 2^{k+1} \).

\( \begin{aligned} \displaystyle \require{ASMSymbols} \require{color}

\text{ LHS } &= (k+1)! \\

&= (k+1) \times k! \\

&\gt (k+1) \times 2^k &\color{red}{\text{ by the assumption from Step 2}} \\

&\gt 2 \times 2^k &\color{red}{k+1 \ge 5 \gt 2} \\

&= 2^{k+1}

\end{aligned} \)

Therefore it is true for \( n=k+1 \), assuming it is true for \( n=k \).

Therefore it is true for \( n! \ge 2^n \) is true for \( n \ge 4 \)

### Example 5

Prove \( 2n+1 \lt 2^n \) for all integers \( n\gt 3 \).

Step 1: Show it is true for \( n=3 \).

LHS \( = 2 \times 3 +1 = 7 \)

RHS \( = 2^3 = 8 \)

LHS \( \lt \) RHS

It is true for \( n=3 \).

Step 2: Assume it is true for \( n=k \).

That is, \( 2k+1 \lt 2^k \).

Step 3: Show it is true for \( n=k+1 \).

That is, \( 2(k+1)+1 \lt 2^{k+1} \).

\( \begin{aligned} \displaystyle \require{ASMSymbols} \require{color}

\text{ LHS } &= 2(k+1)+1 \\ &= 2k+2+1 \\ &= (2k+1) +2 \\ &\lt 2^k+2 \\ &\lt 2^k+2^k \\ &= 2 \times 2^k \\ &=2^{k+1}

\end{aligned} \)

Therefore it is true for \( n=k+1 \), assuming it is true for \( n=k \).

Therefore it is true for \( 2n+1 \lt 2^n \) is true for \( n \gt 4 \)

## Frequently Asked Questions

### What is mathematical induction, and why is it useful in solving inequalities?

Answer: Mathematical induction is a powerful proof technique to establish the truth of statements for an infinite set of natural numbers. It’s especially useful for inequalities because it allows us to prove that a statement holds for all natural numbers. By using induction, you can confidently demonstrate that an inequality is true for every relevant value.

### Can you explain the steps involved in using mathematical induction to prove inequalities?

Answer: Certainly! The steps for using mathematical induction to prove inequalities are as follows:

**Base Case:**Prove that the inequality holds for the smallest natural number, usually \(1\).**Inductive Hypothesis:**Assume the inequality is true for some arbitrary natural number \(k\).**Inductive Step:**Use this assumption to prove the inequality is also true for \(k + 1\).

By completing these steps, you establish the truth of the inequality for all natural numbers.

### Are there any common mistakes to avoid when using mathematical induction for inequalities?

Answer: A common mistake is assuming that the inequality holds for the next value \(k + 1\) without properly proving it in the inductive step. Always demonstrate how the assumption for \(k\) leads to the truth of the inequality for \(k + 1\). Additionally, be thorough in your base case proof, as an incorrect base case can lead to an incorrect conclusion for all natural numbers.

## Conclusion

Congratulations! You’ve ventured into the realm of mathematical induction and inequality proofs. Armed with this powerful tool, you can confidently tackle a wide range of mathematical challenges. Remember that practice makes perfect, so don’t hesitate to apply these techniques to new problems. With time and experience, you’ll become a master of induction magic, triumphing over inequalities in your mathematical journey.

## Related Links

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Ratio Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume

## Responses